PERAN GURU AKIDAH AKHLAK DALAM MENCEGAH DAMPAK NEGATIF INTERNET PADA PESERTA DIDIK - Suharfani Almaisaroh; Wulan Septy Lenggana; Shafa Editya Rachmawati (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2020)
The problem raised regarding substitute parents at school is the teacher to assist and direct students in preventing the negative impact of the internet due to the inability and indifference of parents in controlling their children at home. Ismail revealed that the achievement process cannot be separated from the role of the teacher, the teacher is a person who helps students to learn in building positive attitudes, increased student curiosity, learning successfully by creating conditions that are suitable for students and placing intellectual logic. as a determination in thinking. The method used to compile papers is to read and take several sources from trusted literature. The result is that teachers of aqidah morals have a very important role as a substitute for parents in school. Students make the teacher a personal reflection in carrying out every moral activity in their life, so because of that in order to give the best to students, the teacher will do anything that leads to positive values ​​for all things related to students. In this case also by providing advice in the form of direction and guidance by applying teachings that adhere to the teachings of the Islamic religion.